Optical and optoelectronic properties of one-dimensional CdS nanostructures - Li, Dehui (2013)
The optical and optoelectronic properties of one-dimensional CdS nanowires and nanobelts have attracted a great deal of attention during past decade owing to their visible range bandgap, excellent optical properties and large surface-to-volume ratio. In this thesis, the photoconductivity spectroscopy and photoluminescence spectroscopy are utilized to investigate the optical and optoelectronic properties in one-dimensional CdS nanostructures, mainly focusing on the laser cooling of semiconductors and related topics. How the surface depletion field and external electric field affect those optical and optoelectronic properties has been systematically studied for the purpose of understanding the mechanism of laser cooling. The surface depletion field can lead to the anomalous buleshift of emission with size beyond quantum confinement regime, while Franz-Keldysh effect, Stark effect and field induced exciton ionization have been identified under external applied electric field in CdS nanowires and nanobelts ionization. The net lase cooling of semiconductors has been achieved for the first time in CdS nanobelts mainly due to the strong electron phonon interaction. In addition, we have demonstrated a proof-of-concept of all solid-state cryocoolers by using the CdS nanobelts. Our findings shed light on the optoelectronic applications and opens up the new territory of designing materials for the laser cooling of semiconductors with strong electron phonon coupling.